A Challenge for Parents? Understanding The Needs of a Psychoeducational Program for Parents of Children with Autism Spectrum Disorder - Saputri, Nanda Erfani; Abidin, Zainal (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
Autism spectrum disorder (ASD) is a disorder with a high prevalence and continues to increase from time to time. ASD is still considered a taboo and a scourge. Whereas ASD is not a disease, but a disorder characterized by a decrease in the quality of individuals in social interactions, communication skills, and repetitive interests and behaviors. Due to the increasing prevalence of ASD and the lack of available information, this study seeks to explore the need for whether a parental assistance program is needed when dealing with a diagnosis of ASD in their child. The research method used in this research is qualitative. Researchers involved 6 participants consisting of 2 parents of children diagnosed with ASD, 2 parents of children with typical development, and 2 therapists who have treated children with special. The sampling technique used is purposive sampling. The findings in this study indicate that not much is known about ASD by parents. Parents do a lot of searching independently but the information obtained is generally limited. Parents are also often still confused about understanding ASD and what actions can be taken to help their child. One of the main problems parents face when dealing with an ASD diagnosis is acceptance. Autism spectrum disorder (ASD) menjadi gangguan dengan prevalensi yang cukup tinggi dan terus meningkat dari waktu ke waktu. ASD masih dianggap tabu dan menjadi momok. Padahal ASD bukanlah suatu penyakit, melainkan sebuah gangguan yang ditandai dengan penurunan kualitas individu dalam interaksi sosial, kemampuan komunikasi, serta minat dan perilaku yang berulang. Dengan prevalensi ASD yang terus meningkat dan kurangnya informasi yang tersedia, penelitian ini bertujuan untuk menggali kebutuhan apakah suatu program psikoedukasi bagi orang tua dibutuhkan ketika menghadapi diagnosa ASD pada anaknya. Metode penelitian yang dilakukan dalam penelitian ini adalah kualitatif. Peneliti melibatkan 6 orang partisipan yang terdiri dari 2 orang tua dengan anak terdiagnosa ASD, 2 orang tua dari anak dengan perkembangan tipikal, dan 2 orang terapis yang menangani anak berkebutuhan khusus. Teknik sampling yang digunakan adalah purposive sampling. Temuan dalam penelitian ini menunjukkan bahwa pengetahuan mengenai ASD belum banyak diketahui oleh para orang tua. Orang tua banyak melakukan pencarian secara mandiri namun informasi yang didapat umumnya terbatas. Orang tua juga seringkali masih mengalami kebingungan dalam memahami ASD dan tindakan apa yang dapat dilakukan untuk membantu anak mereka. Salah satu permasalahan utama yang dihadapi orang tua ketika menghadapi diagnosa ASD adalah penerimaan.